Simplify the question
Attachments:
![](https://hi-static.z-dn.net/files/d06/2d50337b945bd6b968646c083b37ac6b.jpg)
Answers
Answered by
3
Hey !!
Here is your answer !!
______________
answer will be 5
How ?
Check the picture attached !
_____
Hope it will help u☺
Here is your answer !!
______________
answer will be 5
How ?
Check the picture attached !
_____
Hope it will help u☺
Attachments:
![](https://hi-static.z-dn.net/files/db3/a46b517b42a44383e9cda50a7ba80fe0.jpg)
kunal421:
yes it s 5
Answered by
1
---------------------------------------------------------------------------------------------------------
= 64 ^ -1/3 [ 64^1/3 + 64 ^ 2/3 ]
= [ ( 64^ -1/3 * 64^ 1/3 ) + ( 64 ^ -1/3 * 64 * 2/3 ]
= [ 64 ^ ( -1/3 + 1/3 ) + 64 ^ ( -1/3 + 2/3 ) ]
-1 + 2
= [ 64^0 + 64 ^ ( ------ ---) ]
3
= [ 1 + 64 ^ 1/3 ]
=[ 1 + ( 4 ^ 3 ) ^ 1/3 ]
= [ 1 + 4 ( 3 * 1/3 ) ]
= [ 1 + 4 ^ 1 ]
= [ 1 + 4 ]
= 5.
---------------------------------------------------------------------------------------------------
= 64 ^ -1/3 [ 64^1/3 + 64 ^ 2/3 ]
= [ ( 64^ -1/3 * 64^ 1/3 ) + ( 64 ^ -1/3 * 64 * 2/3 ]
= [ 64 ^ ( -1/3 + 1/3 ) + 64 ^ ( -1/3 + 2/3 ) ]
-1 + 2
= [ 64^0 + 64 ^ ( ------ ---) ]
3
= [ 1 + 64 ^ 1/3 ]
=[ 1 + ( 4 ^ 3 ) ^ 1/3 ]
= [ 1 + 4 ( 3 * 1/3 ) ]
= [ 1 + 4 ^ 1 ]
= [ 1 + 4 ]
= 5.
---------------------------------------------------------------------------------------------------
Similar questions